Customary vs state laws of land governance: Adivasi joint family farmers seek policy support The case of Kurichya joint families in Wayanad, southern India - T. R. Suma (International Land Coalition and M.S. Swaminathan Research Foundation, 2014)
This research into the land governance system of Kurichya joint family farmers in southern India explains how the traditional social organisation and customary property rights laws of the community have evolved to fit with its ecological and political settings in such a way as to prevent land fragmentation and alienation. Informed by ethnographic methods, this paper argues that the Kurichya system, which functions through kinship relations, matrilineal property succession, rituals, and communal labour arrangements, is a unique model of land governance based on collective ownership, collective farming, and equitable resource sharing. Kurichya joint families follow a sustainable system of natural resource management that ensures ecosystem continuity, natural recycling of organic matter and water, and protection of agro‐biodiversity to ensure future food security. However, centralised state laws on land governance and development policies do not allow political space for systems such as that of the Kurichya and often conflict with them. This paper calls for urgent political attention and changes in policy to ensure the inclusion of pluralistic systems like that of the Kurichya into the wider food production system. T.R. Suma is a Social Researcher at the M.S. Swaminathan Research Foundation in Wayanad, Kerala, southern India. A social anthropologist with over ten years of experience among different cultural groups in Kerala, she specialises in conducting participatory and trans‐disciplinary research aimed at informing policy interventions. Her current research interests include the micro‐level politics of conservation, resource access and conflicts, and traditional ecological knowledge. Her work includes ethnographies of seven communities of Wayanad, an impact assessment of the implementation of a forest rights act in Kerala, and ethnographic analysis of human‐animal relationships in Wayanad. She has directed 40 short films on the ethnic communities of Wayanad and three films on ecology and conservation.